2023
DOI: 10.1093/jas/skad097
|View full text |Cite
|
Sign up to set email alerts
|

Forages and pastures symposium: an update on in vitro and in situ experimental techniques for approximation of ruminal fiber degradation

Abstract: Static quantification measures of chemical components are commonly used to make certain assumptions about forage or feed nutritive value and quality. In order for modern nutrient requirement models to estimate intake and digestibility more accurately, kinetic measures of ruminal fiber degradation are necessary. Compared to in vivo experiments, in vitro (IV) and in situ (IS) experimental techniques are relatively simple and inexpensive methods to determine the extent and rate of ruminal fiber degradation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Using univariate analysis methods, Alba et al [20] concluded that the rumen inoculum of cattle in slaughterhouses with unknown data, such as feeding, management, sex, breed, and others, can be used as a potential substitute for rumen inoculum obtained from cannulated cattle. However, the authors found some differences, as did other authors who used other sources of ruminal inoculum [36]. Therefore, we believe that multivariate analysis can help us find what is or are the factors that must be taken into account when using this source of rumen inoculum.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Using univariate analysis methods, Alba et al [20] concluded that the rumen inoculum of cattle in slaughterhouses with unknown data, such as feeding, management, sex, breed, and others, can be used as a potential substitute for rumen inoculum obtained from cannulated cattle. However, the authors found some differences, as did other authors who used other sources of ruminal inoculum [36]. Therefore, we believe that multivariate analysis can help us find what is or are the factors that must be taken into account when using this source of rumen inoculum.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, the amount and digestibility of NDF are directly responsible for the increase or decrease in acetate production [39,40]. In an extensive review, Foster et al [36] observed that even if all the variables of the animals used as a source of ruminal inoculum were controlled, the cell wall components of the feed are the main components that could affect the digestibility of dry matter or organic matter in in vitro studies. When equine feces were used as an alternative inoculum source in in vitro trials, significant differences between ruminal inoculum sources were observed for IVDMD and IVNDFD [41].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro rumen batch culture is a technique widely used for predicting the degradability and nutritive value of feed sources ( 23 , 24 ). It is also used to screen the potential of non-conventional additives and feeds, such as biochars, microalgae, and seaweeds ( 6 , 25 , 26 ), to modulate ruminal fermentation and, in particular, to reduce methane production.…”
Section: Discussionmentioning
confidence: 99%